2004
DOI: 10.1111/j.1365-2206.2004.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

‘How come I don’t get asked no questions?’ Researching ‘hard to reach’ children and teenagers

Abstract: Researching 'hard to reach' children and teenagers K Curtis et al .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 12 publications
1
73
0
2
Order By: Relevance
“…It is clear that in the present study, the use of activity-oriented interviews resulted in a greater amount of dialogue from participants than standard interviews. This is important in itself; for a participant group commonly described as 'hard to reach' (Curtis et al, 2004), facilitating dialogue and selfexpression is a valued outcome. However, in order for the novel method to be truly efficacious, it should afford insights into the perceptions and experiences of participants not gained through traditional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that in the present study, the use of activity-oriented interviews resulted in a greater amount of dialogue from participants than standard interviews. This is important in itself; for a participant group commonly described as 'hard to reach' (Curtis et al, 2004), facilitating dialogue and selfexpression is a valued outcome. However, in order for the novel method to be truly efficacious, it should afford insights into the perceptions and experiences of participants not gained through traditional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the use of online questionnaires may circumvent issues of consent and improve access to potential research participants (Curtis, 2004). However, this is not in keeping with ethical guidance that has provided direction on the issue.…”
Section: Ethically Compliant Practicementioning
confidence: 92%
“…While it is possible that for many no additional resources were needed, it could also be that respondents assumed that challenges did not stem from structural factors or from methodological issues, but from their own individual deficits, such as a lack of preparation, understanding of recruitment strategies, or skill in networking with gatekeepers. Internalizing challenges are more likely to occur in environments in which research problems are addressed quietly and not commonly discussed publicly (Curtis, Roberts, Copperman, Downie, & Liabo, 2004). New researchers may assume others do not have these experiences, remain silent in their own struggles, and internalize their challenges.…”
Section: Discussionmentioning
confidence: 99%